Rho GTPases: deciphering the evolutionary history of a complex protein family - Eliáš, Marek; Klimeš, Vladimír (Methods in molecular biology (Clifton, N.J.), 2012)
Rho GTPases constitute a significant subgroup of the eukaryotic Ras superfamily of small GTPases implicated in the regulation of diverse cellular processes, such as the dynamics of the actin cytoskeleton, establishment, and maintenance of cell polarity and membrane trafficking. Whereas a few eukaryotes lack Rho genes, a majority of species typically bear multiple Rho paralogs, raising a question about the origin of the family and the paths of its diversification in individual eukaryotic lineages. In this chapter, we ruminate on several aspects of the evolutionary history of the Rho family and methodological challenges of its reconstruction. First, we provide an updated survey of Rho GTPases in diverse eukaryotic branches, demonstrating almost ubiquitous occurrence of Rho genes across the eukaryotic phylogeny most consistent with the presence of at least one Rho gene already in the last eukaryotic common ancestor. Second, we discuss the obstacles in reconstructing the history of gene duplications giving rise to the extant diversity of Rho paralogs in different species, and point to numerous limitations posed by the current phylogenetic methodology. Third, as a case study demonstrating various issues of data collection, phylogenetic analyses and interpretations of trees, we present an analysis of the Rho family in the fungal kingdom, revealing the existence of at least four separate paralogs (Cdc42, Rac, Rho1, and Rho4) in early fungi and subsequent potentially independent expansions of the family in different fungal subgroups. We conclude with the warning that the currently dominating perception of the Rho phylogeny is biased by the metazoan (and especially vertebrate) perspective, and a new, more global view is to be worked out when a better genome sampling and more adequate methods of phylogenetic inference are employed.
Keywords: houby; multigenová rodina; Fungi; Rho proteiny vázající GTP; molekulární evoluce; fylogeneze; Gene Duplication; Molecular Sequence Data; Gene Deletion; Multigene Family; duplikace genu; sekvence aminokyselin; Animals; zvířata; delece genu; Phylogeny; molekulární sekvence - údaje; rho GTP-Binding Proteins; Evolution, Molecular; Amino Acid Sequence